3D printing ceramic filter and preparation slurry and preparation method thereof

The slurry is prepared by a mixture of photosensitive resin and zirconia with a specific ratio, and combined with DLP3D printing technology and sintering treatment, the problems of low exposure accuracy and low printing efficiency in 3D printed ceramic filters are solved, achieving high porosity and high flow velocity filtering effect.

CN119390444AActive Publication Date: 2025-02-07JINAN SHENGQUAN DOUBLE SURPLUS CERAMIC FILTER

Patent Information

Application Number
CN202411559568.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

During the preparation process, existing 3D printed ceramic filters have problems such as low slurry exposure accuracy and low printing efficiency, resulting in poor porosity of the filter and slow metal liquid filtration flow rate.

Method used

The mixed slurry is prepared using a photosensitive resin premix solution and a zirconia mixture of a specific ratio, mixed by a planetary ball mill and filtered under vacuum, scan-cured in combination with DLP3D printing technology, and then sintered to improve the performance of the filter.

Benefits of technology

It improves the slurry exposure accuracy, increases the porosity of the filter and the metal liquid filtration flow rate, and improves the yield and printing efficiency of 3D printed ceramic filters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117520670000051
    Figure BDA0005117520670000051
  • Figure BDA0005117520670000061
    Figure BDA0005117520670000061
  • Figure BDA0005117520670000062
    Figure BDA0005117520670000062
Patent Text Reader

Abstract

The invention provides a 3D printing ceramic filter as well as preparation slurry and a preparation method thereof. The filter comprises the following components: 90 to 92 weight percent of ZrO2, 4.7 to 4.8 weight percent of MgO, 1.9 to 2.0 weight percent of HfO2 and 1.4 to 1.5 weight percent of SiO2. The slurry exposure precision is improved by adjusting the type and proportion of the monomers and the addition amount of the initiator, so that the porosity of the filter and the flow velocity during molten metal filtration are improved. The yield of the provided 3D printing ceramic filter is high and reaches 80% or above. The organic silicon modified epoxy resin is added into the ceramic slurry, so that the printing efficiency is improved. And the anti-settling wax can solve the problem of quick settling of the slurry and improve the problems of appearance cracks and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing, and in particular relates to a 3D printed ceramic filter and a preparation slurry and a preparation method thereof. Background Art

[0002] In the foundry industry, foam ceramic filters are usually used to filter high-temperature metal solutions, because the porous structure of foam ceramic filters can filter out a large amount of impurities contained in the solution and purify the metal solution. The basic materials of foam ceramic filters are silicon carbide, zirconium oxide, and aluminum oxide. The conventional preparation method of foam ceramic filters is generally to use polyurethane foam plastic as a precursor, dip and hang refractory slurry, extrude, dry and then sinter at high temperature. The foam ceramic filter prepared by this method has the following disadvantages: 1. After dipping and hanging refractory slurry, the excess slurry cannot be completely squeezed out during extrusion, resulting in pore blocking and low filter porosity; 2. Because the carrier is foamed polyurethane foam, the internal ribs of the foam are of different thicknesses, resulting in different thicknesses of ribs in foam ceramic filtration, and thinner ribs are easy to break; 3. Due to the limitations of polyurethane foam plastics, foam ceramic filters cannot be made into any shape and cannot meet all needs.

[0003] As a kind of additive manufacturing, 3D printing does not require molds during the production process. It can be made into shapes and internal structures that meet various requirements. Multiple holes can be designed between the inlet and outlet surfaces of a single ceramic unit, and these holes can be evenly distributed, and the size and spacing can be adjusted at will. Adjustments can be made for different filtering requirements to improve the filtering effect. However, the existing 3D printed filters have problems with low slurry exposure accuracy and low printing efficiency during the preparation process. The exposure accuracy of the slurry refers to the fit between the template itself and the remaining part of the slurry after the slurry is evenly spread on the cover glass, exposed according to the template, and washed away after the exposure. The higher the fit, the better the accuracy. The slurry exposure accuracy will directly affect the details of the printed model. If the accuracy is low, the printed details will be rough. For filters, low slurry exposure accuracy will result in poor through-holes, thereby affecting the flow rate of the metal liquid during filtration.

[0004] Chinese patent document CN112225580A (202010957990.3) discloses a photocurable 3D printed zirconia foam ceramic filter and a preparation method thereof. The photocurable 3D printed zirconia foam ceramic filter includes 70-90% zirconium oxide powder and 10-30% photocurable resin by mass fraction. The present invention combines 3D printing technology with high-temperature resistant zirconia ceramic materials. It does not require a porous polyurethane plastic carrier, and can directly form a ceramic foam ceramic filter blank. After high-temperature sintering, a zirconia foam ceramic filter is obtained. The skeleton of the photocurable 3D printed zirconia foam ceramic filter is a solid structure with high strength and is not easy to break. There is no clogging problem caused by excess slurry between the skeletons, so the opening rate is high and the filtering performance is guaranteed. Although this patent has a high opening rate, the exposure accuracy is low, resulting in roughness around the hole, thereby affecting the actual porosity. Summary of the invention

[0005] In order to solve the problems of low precision, poor porosity and slow filtration rate of molten metal in 3D printed filters caused by low slurry exposure precision, the present invention provides a 3D printed ceramic filter and a slurry and method for preparing the same.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A 3D printed ceramic filter, the filter comprises 90-92wt% ZrO2, 4.7-4.8wt% MgO, 1.9-2.0wt% HfO2, 1.4-1.5wt% SiO2, and also contains a small amount of Al2O3, CaO, and TiO2.

[0008] The present invention also provides a mixed slurry for preparing the above-mentioned 3D printed ceramic filter, the slurry comprising the following components in parts by weight: a photosensitive resin premix consisting of 5-15 parts of monomer a, 3-9 parts of monomer b, 2-6 parts of monomer c, 0.02-0.4 parts of an initiator, 0.7-2.7 parts of a dispersant, and 70-90 parts of a zirconium oxide mixture, wherein the zirconium oxide mixture consists of zirconium oxide powder and magnesium oxide powder, wherein the content of magnesium oxide powder is 2-10wt% of the zirconium oxide mixture;

[0009] The monomer a and the monomer b are selected from two of hexylene glycol diacrylate HDDA, tripropylene glycol diacrylate TPGDA, hydroxyethyl acrylate HEA, polyethylene glycol diacrylate PEG (200) DA, and ethylene glycol dimethacrylate EGDMA;

[0010] The monomer c is selected from urethane dimethacrylate UDMA.

[0011] Preferably, the monomer a is hexanediol diacrylate HDDA, the monomer b is hydroxyethyl acrylate HEA, and the monomer c is dimethacrylate urethane UDMA.

[0012] Preferably, the slurry comprises the following components in parts by weight: 10-12 parts of monomer a, 6-8 parts of monomer b, 4-5 parts of monomer c, 1.5-1.6 parts of dispersant, 0.1-0.2 parts of initiator, and 75-80 parts of zirconium oxide mixture.

[0013] Further preferably, the slurry comprises the following components in parts by weight: 10 parts of monomer a, 6 parts of monomer b, 4 parts of monomer c, 1.6 parts of dispersant, 0.2 parts of initiator, and 80 parts of zirconium oxide mixture. Preferably, the zirconium oxide mixture contains 5wt% of magnesium oxide.

[0014] Preferably, the dispersant is selected from BYK111, BYK163, and BYK180, and BYK111 is more preferred.

[0015] Preferably, the initiator is selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyl-xylylphosphine oxide, and more preferably bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0016] Preferably, the particle size of the zirconium oxide mixture is 325-800 mesh, more preferably 800 mesh.

[0017] Preferably, the mass ratio of the monomer (a+b+c) to the zirconium oxide mixture is 10-30:90-70; the mass ratio of the initiator to the monomer (a+b+c) is 1:500-1:50, more preferably 1:200-1:100; the mass ratio of the dispersant to the zirconium oxide mixture is 1:30-1:80, preferably 1:50.

[0018] The present invention solves the problems of low filter accuracy, poor porosity and slow filtration velocity of molten metal in 3D printing caused by low slurry exposure accuracy by using certain raw material types and ratios.

[0019] Preferably, the mixed slurry further contains 3-10% of the mass of the photosensitive resin premix, and the solid content of the silicone-modified epoxy resin is 50±1%. Without the silicone-modified epoxy resin, the printing time for printing one layer is 17 seconds, and after adding the silicone-modified epoxy resin, the printing time for printing one layer is 15 seconds. The addition of the silicone-modified epoxy resin improves the printing efficiency.

[0020] Preferably, the mixed slurry further contains a liquid sintering aid, which accounts for 0.5-1.5wt% of the mixed slurry mass. The liquid sintering aid is polyethylene glycol.

[0021] Preferably, the mixed slurry further contains anti-settling wax, which accounts for 1.5-2.5wt% of the mixed slurry. The anti-settling wax is polyamide wax. The anti-settling wax can solve the problem of rapid slurry sedimentation and improve the problems of cracks in the appearance.

[0022] Further preferably, the mixed slurry further contains 1% of the mass of the mixed slurry of a liquid sintering aid, 2% of an anti-settling wax, and 5% of an organosilicon-modified epoxy resin.

[0023] The present invention also provides a method for preparing the above 3D printed ceramic filter, comprising the following steps:

[0024] (1) preparing a mixed slurry: firstly, monomer a, monomer b, monomer c and initiator are mixed for 20-30 minutes using a planetary ball mill to obtain a photosensitive resin premix; then, zirconium oxide mixture and dispersant are added, and mixing is continued for 30-40 minutes to obtain a mixed slurry;

[0025] (2) preparing ceramic slurry: filtering the mixed slurry through a suction filtration device, and then placing it in a vacuum pump to evacuate for 10-20 minutes to obtain a ceramic slurry;

[0026] (3) 3D printing: Use 3D modeling software to build a 3D printing model of the ceramic filter. Use the software provided by the printer to decompose the model into a series of slices with a thickness of 50-100 μm. Input the established 3D printing model data into the DLP 3D printer and set the printing parameters: the exposure power is 10-30 mw / cm 2 , the first layer printing time is 10-20s, and the material thickness is 50-150μm;

[0027] The ceramic slurry is scanned and solidified according to the above printing parameters. After printing, the ceramic filter is removed from the forming table and the excess slurry is washed away to obtain a ceramic filter embryo.

[0028] (4) Sintering: The printed ceramic filter blank is heated to 900-1200°C at a heating rate of 1-2°C / min, kept at this temperature for 0.5-2h, then heated to 1600-1700°C at a heating rate of 0.5-2°C / min, kept at this temperature for 1-3h, and naturally cooled to room temperature to obtain a 3D printed ceramic filter.

[0029] Preferably, in step (1), silicone-modified epoxy resin, liquid sintering aid and anti-settling wax are added to the photosensitive resin premix.

[0030] Beneficial effects of the present invention:

[0031] (1) The present invention improves the exposure accuracy of the slurry by adjusting the type and ratio of the monomers and the amount of the initiator added, thereby increasing the porosity of the filter and the flow rate of the metal liquid during filtration.

[0032] (2) The 3D printed ceramic filter provided by the present invention has a high yield rate of more than 80%, and can further reach more than 98%.

[0033] (3) The addition of silicone-modified epoxy resin to the ceramic slurry of the present invention improves printing efficiency. Anti-settling wax can solve the problem of rapid slurry sedimentation and improve the appearance of cracks and other problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a real picture of the 3D printed ceramic filter sample obtained in comparative example 1;

[0035] Figure 2 The actual picture of the 3D printed ceramic filter sample obtained in Example 1;

[0036] Figure 3 The slurry is prepared without adding anti-settling wax;

[0037] Figure 4 It is a slurry prepared by adding anti-settling wax;

[0038] Figure 5 This is a picture of the exposure accuracy effect of the ceramic slurry obtained in Example 1;

[0039] Figure 6 This is a picture of the exposure accuracy effect of the ceramic slurry obtained in Example 2.

[0040] Figure 7 This is a schematic diagram of the exposure template used for slurry exposure accuracy. DETAILED DESCRIPTION

[0041] The implementation scheme of the present invention will be described in detail below in conjunction with specific examples. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. Among them, the 3D printer used was purchased from Beijing Shiwei Technology Co., Ltd., the HDDA used was Shanghai Guangyi Chemical Co., Ltd., HEA was Guangzhou Yuanxin Materials Co., Ltd., UDMA was Shandong Shoucheng Chemical Co., Ltd., the initiator was Hubei Shineng Chemical Technology Co., Ltd., zirconium oxide was Sanxiang New Materials Co., Ltd., magnesium oxide was Henan Wanshan New Materials Technology Co., Ltd., and the dispersant was German BYK dispersant BYK-111. The silicone-modified epoxy resin used was Shin-Etsu Chemical ES-1001N.

[0042] Example 1

[0043] A 3D printed ceramic filter is prepared according to the following method:

[0044] (1) Preparation of mixed slurry: First, 10 parts by weight of hexanediol diacrylate HDDA, 6 parts by weight of hydroxyethyl acrylate HEA, 4 parts by weight of dimethacrylate urethane UDMA photocurable monomer and 0.1 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide photoinitiator were placed in a ball mill, and mixed for 20 minutes using a planetary ball mill at room temperature and pressure to obtain a photosensitive resin premix. Then, 80 parts by weight of mixed zirconium oxide powder (containing 5 wt% magnesium oxide) and 1.6 parts by weight of dispersant BYK111 were added, and the mixture was mixed in the planetary ball mill for 40 minutes to obtain a mixed slurry.

[0045] (2) Preparation of ceramic slurry: The mixed slurry is filtered through a suction filtration device, and then placed in a vacuum pump for evacuation for 20 minutes to obtain ceramic slurry.

[0046] (3) 3D printing: Use 3D modeling software to create the required 3D printing model (model porosity 65-75%), use the 10dim software provided by the printer to decompose the model into a series of slices with a thickness of 75 μm, input the established 3D printing model data into the DLP3D printer, and set the printing parameters: exposure power is 20 mw / cm 2 The first layer printing time is 18s, and the material thickness is 100μm. The ceramic slurry is placed in the 3D printer material box and scanned and solidified according to the above printing parameters. After printing, the ceramic filter is removed from the forming table and the excess slurry is washed away to obtain the ceramic filter embryo.

[0047] (4) Sintering: The printed ceramic filter blank was heated to 1100°C at a heating rate of 1.5°C / min, kept at this temperature for 1 h, then heated to 1650°C at a heating rate of 1°C / min, kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a 3D printed ceramic filter.

[0048] The preparation methods of other embodiments and comparative examples refer to Example 1. The preparation parameters of each embodiment and comparative example are summarized in Table 1. The parameters not recorded in Table 1 are the same as those in Example 1.

[0049] Example 2

[0050] The difference from Example 1 is that an organosilicon-modified epoxy resin (ES-1001N produced by Shin-Etsu Chemical) is added to the photosensitive resin premix in step (1), and the amount of the organosilicon-modified epoxy resin added accounts for 5% of the weight of the photosensitive resin premix.

[0051] Example 3

[0052] Different from Example 1, the ratio of the mixed slurry is changed, as shown in Table 1.

[0053] Example 4

[0054] The difference from Example 1 is that the initiator is changed to 0.2 parts by weight, and an organosilicon-modified epoxy resin (Shin-Etsu Chemical ES-1001N), polyethylene glycol, and polyamide wax are added to the photosensitive resin premix of step (1) to obtain a mixed slurry. The organosilicon-modified epoxy resin accounts for 5% of the weight of the photosensitive resin premix, the polyethylene glycol accounts for 1% of the total weight of the mixed slurry, and the polyamide wax accounts for 2% of the total weight of the mixed slurry.

[0055] Comparative Example 1

[0056] The difference from Example 1 is that monomer c is trimethylolpropane triacrylate TMPTA.

[0057] Comparative Example 2

[0058] Different from Example 1, the ratio of the mixed slurry and the sintering parameters are changed. The specific process is shown in Table 1.

[0059] Table 1 is the preparation process parameters of each embodiment and comparative example

[0060]

[0061]

[0062] The performance of the ceramic slurries or ceramic filters prepared in the above examples and comparative examples was evaluated, and the results are shown in Table 2:

[0063] Filter performance evaluation method:

[0064] Filter flow rate: 1 square centimeter of molten metal flow rate.

[0065] Exposure accuracy: Spread the slurry on a glass slide, place it in the center of the printer glass plate, and select an exposure template (such as Figure 7 After exposure, the excess slurry is washed off and the hollowed-out part is measured with a vernier caliper. The closer the size is to the size given by the exposure template, the better the exposure effect. In the present invention, the exposure accuracy is arranged in the order of high, relatively high, general, relatively low and poor.

[0066] Yield rate: the percentage of 100 sintered filters with intact appearance to the total number.

[0067] Sedimentation rate: Pour the slurry into a test tube and let it stand for 24 hours. The height of the slurry with stratification / the overall height of the slurry × 100%.

[0068] Curing time: the time (s) taken to cure one layer.

[0069] Filter porosity: Porosity refers to the ratio of the volume occupied by pores in a porous body to the total volume of the porous body. The instrument used for porosity detection is an electronic balance, and the porosity determination method in GB / T25139 is used for determination. The larger the porosity of the filter, the greater the flow rate of the filtered metal liquid, but if the porosity is too large, the filtering effect will also deteriorate.

[0070] Table 2 Performance evaluation results of ceramic slurries or ceramic filters prepared in Examples and Comparative Examples

[0071] serial number Filter porosity Sedimentation rate Exposure accuracy Curing time Yield Example 1 72.8% 10% Higher 18s 88% Example 2 74.6% 10% high 15S 87% Example 3 72.3% 10% high 17S 88% Example 4 73.3 3% Higher 15S 92% Comparative Example 1 62.5 10% Higher 18s 53% Comparative Example 2 65.3% 10% Difference 18s 60%

[0072] It can be seen from Table 1 and Table 2 that the printing accuracy, yield rate, sedimentation rate and printing efficiency of the embodiment are improved compared with the comparative example.

[0073] The filter components were detected by fluorescence analyzer. The filter components analysis of the present invention is shown in Table 3 below:

[0074] Table 3 Component test results of the filter obtained in Example 4

[0075]

[0076]

Claims

1. A 3D printed ceramic filter, characterized in that: The filter comprises 90-92wt% of ZrO2, 4.7-4.8wt% of MgO, 1.9-2.0wt% of HfO2, and 1.4-1.5wt% of SiO2.

2. A mixed slurry for preparing the 3D printed ceramic filter according to claim 1, characterized in that: The slurry comprises the following components in parts by weight: a photosensitive resin premix consisting of 5-15 parts of monomer a, 3-9 parts of monomer b, 2-6 parts of monomer c, 0.02-0.4 parts of an initiator, 0.7-2.7 parts of a dispersant, and 70-90 parts of a zirconium oxide mixture, wherein the zirconium oxide mixture consists of zirconium oxide powder and magnesium oxide powder, wherein the content of magnesium oxide powder is 2-10wt% of the zirconium oxide mixture; The monomer a and the monomer b are selected from two of hexylene glycol diacrylate HDDA, tripropylene glycol diacrylate TPGDA, hydroxyethyl acrylate HEA, polyethylene glycol diacrylate PEG (200) DA, and ethylene glycol dimethacrylate EGDMA; The monomer c is selected from urethane dimethacrylate UDMA.

3. The mixed slurry according to claim 2, characterized in that: The monomer a is hexanediol diacrylate HDDA, the monomer b is hydroxyethyl acrylate HEA, and the monomer c is dimethacrylate urethane UDMA.

4. The mixed slurry according to claim 2, characterized in that: The slurry comprises the following components in parts by weight: 10-12 parts of monomer a, 6-8 parts of monomer b, 4-5 parts of monomer c, 1.5-1.6 parts of dispersant, 0.1-0.2 parts of initiator, and 75-80 parts of zirconium oxide mixture. Preferably, the slurry comprises the following components in parts by weight: 10 parts of monomer a, 6 parts of monomer b, 4 parts of monomer c, 1.6 parts of dispersant, 0.2 parts of initiator, and 80 parts of zirconium oxide mixture. Preferably, the zirconium oxide mixture contains 5wt% of magnesium oxide.

5. The mixed slurry according to claim 2, characterized in that: The dispersant is selected from BYK111, BYK163, and BYK180, preferably BYK111. Preferably, the initiator is selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyl-xylylphosphine oxide, and more preferably bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide. Preferably, the particle size of the zirconium oxide mixture is 325-800 mesh.

6. The mixed slurry according to claim 2, characterized in that: The mass ratio of the monomer (a+b+c) to the zirconium oxide mixture is 10-30:90-70; the mass ratio of the initiator to the monomer (a+b+c) is 1:500-1:50, preferably 1:200-1:100; the mass ratio of the dispersant to the zirconium oxide mixture is 1:30-1:

80.

7. The mixed slurry according to claim 2, characterized in that: The mixed slurry also contains organic silicon modified epoxy resin, which accounts for 3-10% of the mass of the photosensitive resin premixed liquid, and the solid content of the organic silicon modified epoxy resin is 50±1%.

8. The mixed slurry according to any one of claims 2 to 7, characterized in that: The mixed slurry further contains a liquid sintering aid, which accounts for 0.5-1.5wt% of the mixed slurry mass, and the liquid sintering aid is polyethylene glycol; Preferably, the mixed slurry further contains anti-settling wax, and the anti-settling wax accounts for 1.5-2.5wt% of the mass of the mixed slurry.

9. The method for preparing the 3D printed ceramic filter according to claim 1, characterized in that: The following steps are involved: (1) preparing a mixed slurry: firstly, monomer a, monomer b, monomer c and initiator are mixed for 20-30 minutes using a planetary ball mill to obtain a photosensitive resin premix; then, zirconium oxide mixture and dispersant are added, and mixing is continued for 30-40 minutes to obtain a mixed slurry; (2) preparing ceramic slurry: filtering the mixed slurry through a suction filtration device, and then placing it in a vacuum pump to evacuate for 10-20 minutes to obtain a ceramic slurry; (3) 3D printing: Use 3D modeling software to build a 3D printing model of the ceramic filter. Use the software provided by the printer to decompose the model into a series of slices with a thickness of 50-100 μm. Input the established 3D printing model data into the DLP 3D printer and set the printing parameters: the exposure power is 10-30 mw / cm 2 , the first layer printing time is 10-20s, and the material thickness is 50-150μm; The ceramic slurry is scanned and solidified according to the above printing parameters. After printing, the ceramic filter is removed from the forming table and the excess slurry is washed away to obtain a ceramic filter embryo. (4) Sintering: The printed ceramic filter blank is heated to 900-1200°C at a heating rate of 1-2°C / min, kept at this temperature for 0.5-2h, then heated to 1600-1700°C at a heating rate of 0.5-2°C / min, kept at this temperature for 1-3h, and naturally cooled to room temperature to obtain a 3D printed ceramic filter.

10. The method for preparing the 3D printed ceramic filter according to claim 9, characterized in that: In step (1), organic silicon modified epoxy resin, liquid sintering aid and anti-settling wax are added to the photosensitive resin premix.

Citation Information

Patent Citations

  • Zirconium oxide foamed ceramic filter

    CN101259347A

  • Preparation method of magnesium-stabilized zirconium for preparing foamed ceramic filter

    CN110483039A

  • Photocuring 3D printing zirconia foamed ceramic filter and preparation method thereof

    CN112225580A

  • Preparation of ceramic slurry for 3D printing, and 3D printing photocuring molding method thereof

    CN112390626A

  • Dental restoration composition as well as preparation method and application thereof

    CN112494341A

Cited By

  • Composite material ceramic filter screen for casting and photocuring 3D printing preparation method

    CN121377741A